1997
DOI: 10.1002/jor.1100150111
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical changes of the wrist flexor and extensor tendons following loss of scaphoid integrity

Abstract: Loss of integrity of the scaphoid may change the motion center of the entire carpus, and deformities from scaphoid fractures may alter the location of motor tendons of the wrist, thus altering their biomechanics. The goal of this study was to clarify biomechanical changes in these tendons following loss of scaphoid integrity. Excursions and moment arms of the principal flexor and extensor tendons of the wrist were investigated in seven cadaveric upper extremities in intact wrists after simulation of scaphoid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This effect size indicates that the smallest detectable difference in mean moment arm magnitude is approximately 2 mm. The validity of the pre-hoc power analysis was verified by confirming that the effect sizes measured in this study were greater than or equal to those assumed from the literature [26]. …”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…This effect size indicates that the smallest detectable difference in mean moment arm magnitude is approximately 2 mm. The validity of the pre-hoc power analysis was verified by confirming that the effect sizes measured in this study were greater than or equal to those assumed from the literature [26]. …”
Section: Methodssupporting
confidence: 74%
“…Given the paucity of data characterizing how the mechanical actions of muscles change following surgical salvage procedures, it is difficult to interpret the clinical significance of the variability observed across these two studies. In contrast, at least six studies from different investigators have quantified moment arms for the nonimpaired wrist [19, 20, 2326]. For all muscles examined, the nonimpaired moment arms in this study fell within two standard deviations of the average data reported among these six studies (Fig.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Studies related to normative data for grip and pinch are presented in different countries and serve as a reference in clinical practice in order to compare possible changes of grip strength and pinch, arising from different lesions of the upper limb 6,16 . Tang et al 17 describe that changes in biomechanical parameters of the wrist can be an important cause of diseases and dysfunctions. Alizadehkhaiyat et al 18 describe the fatigue as a possible etiology of wrist and elbow dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 When the scaphoid is fractured, its role is accentuated, as the ligaments affect the stability of the fracture fragments. It is, therefore, important for the assessment and repair of scaphoid fractures and/or ligament injuries to have an accurate anatomical knowledge of the ligament attachments and morphology.…”
mentioning
confidence: 99%